Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d1ra05711a
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium equilibrium isotope effects in a supramolecular receptor for the hydrochalcogenide and halide anions

Abstract: We highlight a convenient synthesis to selectively deuterate an aryl C–H hydrogen bond donor in a supramolecular anion receptor and use competitive titrations to study the deuterium equilibrium isotope effects (DEIE) in binding HS−, Cl−, and Br−.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We have introduced a family of arylethynyl bisurea receptors and studied their anion binding ability in homogenous organic solutions. [25][26][27][28][29] The rigidity of the arylethynyl pivot is thought to impart greater anion binding affinity and selectivity in this tweezer-type receptor, which also features an active C-H donor group to complement its four N-H donors. We have also shown that the arylethynyl urea scaffold can be used in the design of receptors capable of selective extraction of hydrogen sulfate from sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…We have introduced a family of arylethynyl bisurea receptors and studied their anion binding ability in homogenous organic solutions. [25][26][27][28][29] The rigidity of the arylethynyl pivot is thought to impart greater anion binding affinity and selectivity in this tweezer-type receptor, which also features an active C-H donor group to complement its four N-H donors. We have also shown that the arylethynyl urea scaffold can be used in the design of receptors capable of selective extraction of hydrogen sulfate from sulfuric acid.…”
Section: Introductionmentioning
confidence: 99%